2009
DOI: 10.1080/01421590802225770
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for blueprinting

Abstract: A well constructed blueprint is a valuable tool for medical educators. In addition to validating evaluation content, a blueprint can also be used to guide selection of curricular content and learning experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 7 publications
0
64
0
4
Order By: Relevance
“…Previous research has also indicated that the use of a blueprint in assessment ensures coverage of all aspects of the curriculum, learning objectives and educational domains. 5,24,25 Very few faculty members and students in the current study believed that the assessment contained questions which were too easy or too difficult; this suggests that the use of a blueprint resulted in a rational paper and avoided construct irrelevance variance. Moreover, the blueprint seemed to make the assessment more 'fair' in the eyes of both faculty members and students.…”
Section: Open-ended Responsesmentioning
confidence: 99%
“…Previous research has also indicated that the use of a blueprint in assessment ensures coverage of all aspects of the curriculum, learning objectives and educational domains. 5,24,25 Very few faculty members and students in the current study believed that the assessment contained questions which were too easy or too difficult; this suggests that the use of a blueprint resulted in a rational paper and avoided construct irrelevance variance. Moreover, the blueprint seemed to make the assessment more 'fair' in the eyes of both faculty members and students.…”
Section: Open-ended Responsesmentioning
confidence: 99%
“…In that case, relevant Milestones would be absent, and therefore, a gap would exist between important behaviors of practice and those of training. Blueprinting, a process of mapping the content of the realworld experience to an assessment tool, 25 is performed with careful attention to content representation and is a potential strategy to mitigate sampling errors.…”
Section: Content and Sampling Errorsmentioning
confidence: 99%
“…Construct under-representation is a pertinent example of this, which occurs when a topic forming only a small part of the curriculum is examined prominently. This not only undermines validity but also can cause huge distress to students (Messick, 1989, Coderre, Woloschuk & Mclaughlin, 2009. In order to avoid this, there are many models we can use for an assessment blueprint including Miller's pyramid (1990), Bloom's taxonomy (1956) and the Dreyfus and Dreyfus (1980) spectrum of skills acquisition to name but a few.…”
Section: Introductionmentioning
confidence: 99%